Seismic Strength and Stiffness for Recycled Aggregate Concrete-Filled Steel Tube Frame - Xianggang Zhang; Jianhui Yang; Yaozong Zhang; Xiang Gao (Advances in Civil Engineering)
To study the seismic strength and stiffness for recycled aggregate concrete-filled steel tube (RACFST) frame, two-frame specimens made up of RACFST column and reinforced recycled aggregate concrete (RAC) beam were used for a seismic test under reversed low-cycle loading. The failure mechanism, hysteresis curve, strength attenuation, and stiffness degradation were determined for the specimens. The design methods for the story shear bearing capacity and stiffness for the single-layer single-span RACFST frame were discussed. It is shown that the seismic design requirements including “strong column weak beam” and “strong shear weak bending” can be met. The hysteresis curves are symmetric and the strength attenuation and rigidity degeneration change significantly, then change a little, and then significantly again under the same displacement. It is possible that the methods including elastic bending moment at the column end, plastic hinge at the column end, and plastic hinge at the column bottom can all be applied to the design calculation of the story shear bearing capacity for the single-layer single-span RACFST frame. The method adopted in this paper can be used to estimate the original elastic layer stiffness of the RACFST frame.